Multi-state System Reliability Analysis Based on Fuzzy Colored Petri Nets. (10th February 2017) - Zhang, Xin-ju
Abstract: In a multi-state system, because of performance degradation or partial failure, the system or its components could exist in a series of intermediate states between the perfect state and the failure state. These intermediate states will directly influence the system reliability. To address this problem, the fuzzy colored Petri nets (FCPNs) method is proposed. The model fully characterizes the multi-state reliability through fuzzy state information and the dynamic transition between state nodes in the fuzzy colored Petri nets, and the weighted threshold will change with the dynamic change of fuzzy information and node state changes. Therefore, the adaptive fuzzy reasoning algorithm of threshold adjustment is proposed, which provides sufficient model guidance for multi-state system reliability analysis and performance optimization. Multi-state reliability is verified, which shows that the FCPNs and the parameter adjustment strategy are reasonable and effective and improve the overall performance of the multi-state system.